Entrepreneurship for Economic and Social Empowerment of Women: A Case Study of a Self Help Credit Program in Nithari Village, Noida, India - Shikha Kapoor (Australasian Accounting, Business and Finance Journal, 2019)
In modern times a nation cannot afford to have any of its citizens who are capable of economic development to be non-productive. However, the resource crunch, lack of skills and financial paucity leads to 75% people being unemployed. This can be elevated through interventions of Government by giving directions and purpose for their livelihood. Empowerment is the ability to gain power over oneself and take decisions over one’s life. It boosts the confidence, self-esteem, wellbeing and control over one owns life. The study explores the influence, through focus group discussions and interviews, of self-help groups, which can contribute towards economic development and livelihood programs to make a difference in the life of citizens below the poverty line. The paper brings out the effectiveness of social mobilisation and economic development by presenting the cases and demonstrates how they are making a difference in society. It tries to analysis how SHG as a part of social innovation can be used for empowering women /girls through entrepreneurship alleviation. It also reveals its social and economic implications by women involvement in productive and financial contribution in the family hence addressing the importance of SHG’s and its progressive development of women .New public policies can be designed to strengthen and pave the way for financing these SHG (Self Help Group). Corporates can be encouraged to adopt regions to support SHG as part of mandatory CSR (Corporate Social responsibility) activity as per Companies Act 2013 in India. This paper summarizes how self-help groups may promote awareness among the members if they are provided with sufficient opportunities for empowerment to combat poverty. Besides, involvement in SHG’s has enabled members to voice their opinions on community affairs, and it has also helped in gaining freedom, self-confidence, self-identity to tackle problems and gaining power over decision making in the household.
Keywords: India; Women; Poverty alleviation; society; sustainable; empowerment; microfinance; SHG.